Evaluation of Liquidity, Capital Structure, and Risk Management Challenges in Maintaining Company Financial Stability - Muchsidin, Feronika Fungky; Ramlah, Ramlah; Samalam, Abdul Gafar; Wahab, Abdul; Lawalata, Izaac L D (Advances in Management & Financial Reporting, 2025)
Purpose: This research aims to evaluate the challenges companies face in maintaining financial stability through the integrated management of liquidity, capital structure, and risk management. The study examines how these elements interact and impact corporate financial resilience, particularly during periods of global economic uncertainty. Research Method: The study adopts a qualitative systematic literature review approach, analyzing recent research and theoretical frameworks related to liquidity management, capital structure, and risk management. This method enables a comprehensive examination of how these financial elements contribute to overall corporate stability across various sectors, with a primary focus on the e-commerce industry. Results and Discussion: The research reveals that effective liquidity management enables companies to meet their short-term obligations while maintaining operational flexibility. A balanced capital structure reduces financial risks, while proactive risk management strategies, such as hedging and diversification, mitigate exposure to market volatility. The integration of these elements allows firms to navigate economic disruptions more effectively. Additionally, the role of technology in enhancing real-time financial decision-making is emphasized as a critical factor in maintaining long-term financial stability. Implications: The study highlights the practical and managerial importance of adopting an integrated approach to liquidity, capital structure, and risk management. Business leaders are encouraged to leverage digital technologies to enhance financial management practices, ensuring corporate resilience in a rapidly changing global market. Policymakers can also use these insights to inform regulatory frameworks that support the financial stability of various industries.